Is vitamin C able to reduce hyperuricemia - S., Hantono (International Journal of Research in Medical Sciences, 2019)
Hyperuricemia is defined as high levels of blood uric acid, the product of purine metabolism, which can form uric acid crystals and lead to become gout. Gout is a systemic disease that results from chronic elevation of uric acid levels above the threshold point and form the deposition of monosodium urate (MSU) crystals in tissues, mainly in and around the joints forming tophi. The impact of gout and its associated conditions can cause deformity, morbidity and mortality. Vitamin C is shown to has beneficial effect in lowering serum uric acid level in hyperuricemia patients with unknown mechanism. But it is still debatable whether using or not using and the dose of vitamin C because giving large doses also had no effect on serum uric acid concentration, uric acid excretion and clearance by the kidney, and even can cause adverse effects.